2022
DOI: 10.3389/fimmu.2022.907605
|View full text |Cite
|
Sign up to set email alerts
|

Myeloid Cell Classification and Therapeutic Opportunities Within the Glioblastoma Tumor Microenvironment in the Single Cell-Omics Era

Abstract: The glioma tumor microenvironment (TME) is complex and heterogeneous, and multiple emerging and current technologies are being utilized for an improved comprehension and understanding of these tumors. Single cell analysis techniques such as single cell genomic and transcriptomic sequencing analysis are on the rise and play an important role in elucidating the glioma TME. These large datasets will prove useful for patient tumor characterization, including immune configuration that will ultimately influence ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 62 publications
2
9
0
Order By: Relevance
“…Recent immunophenotyping studies have revealed that the glioma TIME is characterized by a heterogeneous, predominantly myeloid population (Chen et al, 2017) (Larkin et al, 2022) (Gupta et al, 2022 Preprint). These myeloid cells include yolk sacderived brain resident microglia (MG), bone marrow-derived macrophages (MACs), and monocyte-derived macrophages (MDMs) (Morantz et al, 1979) (Gupta et al, 2022 Preprint).…”
Section: Introductionmentioning
confidence: 99%
“…Recent immunophenotyping studies have revealed that the glioma TIME is characterized by a heterogeneous, predominantly myeloid population (Chen et al, 2017) (Larkin et al, 2022) (Gupta et al, 2022 Preprint). These myeloid cells include yolk sacderived brain resident microglia (MG), bone marrow-derived macrophages (MACs), and monocyte-derived macrophages (MDMs) (Morantz et al, 1979) (Gupta et al, 2022 Preprint).…”
Section: Introductionmentioning
confidence: 99%
“…Our IMC data, along with published single-cell sequencing studies, demonstrate that myeloid cells exist in a spectrum of activation states in GBM ( 7 , 18 ) with the polarization of myeloid cells toward either microglia or TAMs being the most prominent ( 22 , 28 , 29 ). However, the exact ontogeny of the identified myeloid populations in GBM remains unclear ( 4 ). We therefore used partition-based graph abstraction (PAGA) analysis to understand the relationships between the seven myeloid populations identified by IMC (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…As such, they are viewed as attractive targets for novel treatments for GBM, with preclinical data supporting the benefit of macrophage modulation (3). However, the myeloid cell compartment is extremely heterogeneous in GBM, being able to adopt a spectrum of proinflammatory and suppressive states (4,5) with immunosuppressive phenotypes being associated with worse outcome (6)(7)(8)(9)(10)(11).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations